Child abuse, child protection and the law - Cleland, Alison (Thomson/W. Green, 2008)
"This is the first Scottish text to analyse the law relating to child abuse in terms of prevention, protection, and proactivity. This is the first book to consider both civil and criminal child protection measures relating to the protection of children and the prosecution of sexual offences. The child is kept at the centre of all discussion as the text attempts to identify the consequences for the child of the various legal mechanisms which may be used. This book will be of value for lawyers, social workers, police, medical practitioners, educators and children's organisations working in the field of child protection."--BOOK JACKET